Survei Keterampilan Passing Bawah Pada Team Bola Voli Putra STKIP Kie Raha Ternate - Mahatma Raison Pribadi (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is a descriptive study that describes the ongoing situation or situation without proposing a hypothesis, Suharsimi Arikunto (2006: 32) states that "descriptive research is not intended to test certain hypotheses, but only describes "what is" about a variable, symptom or situation". The method used in this research is a survey with test and measurement techniques. Population is the whole research subject (Suharsimi Arikunto, 2002: 108). The population in this study was the STKIP Kie Raha Ternate Men's Bolavoli Team with a total of 18 people. Based on the results of data analysis and the formulation of problems that have been found, it shows that the upper passing skills of the STKIP Kie Raha Ternate women's volleyball team are in the sufficient category. This is reinforced by data analysis where there are 2 people or 11.11% in the very good category, and a good category of 3 people by 16.67%, a sufficient category is obtained by 8 people or 44.44%, then for the category less obtained by 4 people or 22.22% and for the category very less obtained by 1 person or 5.56%. If this is related to the theories that have been put forward, basically what supports the results of this study is that the high or low level of upper passing skills in the women's volleyball team is strongly influenced by the strategic technique of presenting material by the coach, available facilities and infrastructure. As is the case for the STKIP Kie Raha Ternate Women's Bolavoli Team, there are several people who have accurate upper passing skills, and vice versa there are several people who have not been able to do the upper pass well.